Study of Mixed Spin (1, 3/2) in Ferrimagnetic Ising Nanowire - Hadey K.; Omar M.; Hassan A. (University of Thi-Qar Journal, 2020)
A ferrimagnetic mixed spin square Blume-Capel Ising nanowire system depend of spin-1 core and spin-3/2 outer shell have been investigated. The general formula for the temperature dependence of the equilibrium magnetization of the system is presented. The ferrimagnetic core-shell nanosystem shows a compensation point when the exchange interactions are changed at various values of the single-ion anisotropies of shell sublattices and core ones, respectively. So, one can examine interesting phenomena are compensation behaviors and the free energy of the nanosystem, where these phenomena found that the mixed-spin square Blume-Capel Ising nanosystem which is being considered has two spin compensation temperatures in the range of , when , for two different values of core anisotropy for sublattices of atoms A, , and , respectively.